Comparing the Effectiveness of Platelet‐Rich Plasma Alone Versus Combined With Microneedles or Radiofrequency for Neck Wrinkle Treatment - Li, Ke‐Cheng; Lin, Zi‐Zhe; Zhang, Zhi‐Dan; Xie, Shan; Xie, Guang‐Hui (Journal of cosmetic dermatology, 2025)
ABSTRACT Background Neck wrinkles are a prominent characteristic of skin aging, with recent studies indicating that interventions such as platelet‐rich plasma (PRP), microneedling (MN), and radiofrequency (RF) can effectively rejuvenate aging skin. Aims This study aims to assess and compare the efficacy of three treatment modalities in addressing neck wrinkles. Methods Fifteen female participants with a neck Lemperle Wrinkle Assessment Scale (WAS) score of 3–4 were enrolled in a randomized clinical trial. The subjects were randomly assigned to three treatment groups: PRP injection, MN + PRP topical PRP application, and RF + PRP injection. They received treatment once a month for three consecutive months, and a clinical outcome evaluation was performed at 1 and 6 months after the final treatment. Results The WAS scores and global aesthetic improvement score (GAIS) demonstrated notable enhancements 1 month postfinal treatment across all three groups, with a notably greater number of participants experiencing improved outcomes in the RF + PRP group 6 months posttreatment. Specifically, at the 1‐month follow‐up, the RF + PRP group exhibited a statistically significant enhancement in skin elasticity and collagen, surpassing the improvements observed in the other two groups (p < 0.05). No significant disparities in skin elasticity and collagen were detected in all groups prior to and after 6 months of treatment. Adverse events were mild and transient, such as redness, swelling, bruising, and pain. Conclusion This study revealed that all the treatments can effectively improve neck wrinkles 1 month after the last treatment. A better therapeutic effect could be observed in the RF + PRP group compared with the other two groups at 6 months after the last treatment.